2017
DOI: 10.1016/j.pediatrneurol.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram Coherence Patterns in Autism: An Updated Review

Abstract: Recent electrophysiological studies suggest that autism spectrum disorder is characterized by aberrant anatomical and functional neural circuitry. During normal brain development, pruning and synaptogenesis facilitate ongoing changes in both short- and long-range neural wiring. In developmental disorders such as autism, this process may be perturbed leading to abnormal neural connectivity. Careful analysis of electrophysiological connectivity patterns using EEG coherence may provide a way to probe the resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 87 publications
(233 reference statements)
2
44
0
Order By: Relevance
“…Given that some studies show that ASD patients and controls have similar FRN amplitudes to reward and punishment feedback (Larson et al, 2011; McPartland et al, 2012), these data underscore the importance of also measuring the consistency of trial-to-trial phase alignment as a measure of neural synchrony. In a reward prediction task we show a unique difference, lower trial-to-trial phase locking in ASD, consistent with several studies highlighting a lack of neural synchrony as an endophenotype in ASD (Catarino et al, 2013; David et al, 2016; Dinstein et al, 2011; Lushchekina et al, 2016; Schwartz et al, 2016). Our findings point to further evidence for reduced ITC in ASD and the benefit of examining more nuanced measures in EEG studies that can differentiate ASD from neurotypical controls.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Given that some studies show that ASD patients and controls have similar FRN amplitudes to reward and punishment feedback (Larson et al, 2011; McPartland et al, 2012), these data underscore the importance of also measuring the consistency of trial-to-trial phase alignment as a measure of neural synchrony. In a reward prediction task we show a unique difference, lower trial-to-trial phase locking in ASD, consistent with several studies highlighting a lack of neural synchrony as an endophenotype in ASD (Catarino et al, 2013; David et al, 2016; Dinstein et al, 2011; Lushchekina et al, 2016; Schwartz et al, 2016). Our findings point to further evidence for reduced ITC in ASD and the benefit of examining more nuanced measures in EEG studies that can differentiate ASD from neurotypical controls.…”
Section: Discussionsupporting
confidence: 90%
“…Some evidence suggest that within-subject variability in the amplitude and timing of early visual P1 ERPs is greater in ASD compared to neuro-typical matched controls (Milne, 2011). Others have examined neural variability in youth and young adults with ASD and found low coherence across multiple frequency bands during resting states (Dinstein et al, 2011; Lushchekina, Khaerdinova, Novototskii-vlasov, & Lushchekin, 2016), stimulus processing (Catarino et al, 2013), and cognitive tasks (Lushchekina et al, 2016), leading some to suggest that a lack of synchrony in neural oscillations reflects an endophenotype of ASD (David et al, 2016; Schwartz, Kessler, Gaughan, & Buckley, 2016). Thus, we consider whether this variability could also be present in the FRN and reflect a lack of synchronization in medial frontal neural systems that mediate feedback processing.…”
Section: Introductionmentioning
confidence: 99%
“…Although the relationships between behavior and oscillatory activity were not tested directly in the present study, some relationships might be hypothesized from prior work, where decreased theta and alpha coherence were shown to lead to impairment in working memory and between-network binding (particularly as related to executive processing, inhibition, and conscious attention), while beta frequency synchrony has been related to successful higher-order cognitive processing (cf. Schwartz et al, 2017). Additionally, atypical pattern of synchronization in the left hemisphere might be related to leftlateralized microstructural abnormalities in ASD (Peterson et al, 2015) Our analysis of fronto-parietal temporal dysregulation suggests a possible underlying mechanism whereby normal functional organization of brain networks in ASD fails to emerge.…”
Section: Discussionmentioning
confidence: 91%
“…Coherence provides a measure of the degree of synchronization between two signals, which means that the two signals with the same frequency have the consistent phase relationship over time, and we could also assume there is a high degree of the coordinated brain activity between the underlying brain areas where those two signals come from . EEG coherence is one way to assess the brain functional connectivity, which has proven abnormal in previous studies for ASD children .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that abnormalities in brain network connectivity were common in autistic children, which might lead to atypical interactions between brain regions that could lead to the social and cognitive impairment . For ASD, the ongoing changes of the pruning and synaptogenesis disturbed the normal brain development, thus leading to the abnormal neural connectivity . Therefore, differences in EEG signals can be used to compare the children with autism with the typical developmental children .…”
Section: Introductionmentioning
confidence: 99%